2020
DOI: 10.1126/sciimmunol.aba0925
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine deaminase 2 is required for VLRB antibody gene assembly in lampreys

Abstract: The antibodies of jawless vertebrates consist of leucine-rich repeat arrays encoded by somatically assembled VLRB genes. It is unknown how the incomplete germline VLRB loci are converted into functional antibody genes during B lymphocyte development in lampreys. In Lampetra planeri larvae lacking the cytidine deaminase CDA2 gene, VLRB assembly fails, whereas the T lineage–associated VLRA and VLRC antigen receptor gene assemblies occur normally. Thus, CDA2 acts in a B cell lineage–specific fashion to support th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…The dashed box around proto-CDA2 and proto-VLR indicate that these were subsequently exapted to underpin the adaptive immune systems of jawless fishes, comprising hagfishes and lampreys (upper brown boxes). In lampreys, it has now been demonstrated that CDA2 is required for VLRB receptor gene assembly [ 20 •• ]; likewise, it is assumed but not yet proven that CDA1 assembles VLRA/C receptor genes. In hagfishes, the VLR/CDA system might operate in a similar fashion; however, since the repertoire of AAD genes in this group of animals remains uncharacterized, their potential roles in the assembly of VLRA/C are unknown.…”
Section: The Origins Of the Rag Recombinase And Split Antigen Receptomentioning
confidence: 99%
See 4 more Smart Citations
“…The dashed box around proto-CDA2 and proto-VLR indicate that these were subsequently exapted to underpin the adaptive immune systems of jawless fishes, comprising hagfishes and lampreys (upper brown boxes). In lampreys, it has now been demonstrated that CDA2 is required for VLRB receptor gene assembly [ 20 •• ]; likewise, it is assumed but not yet proven that CDA1 assembles VLRA/C receptor genes. In hagfishes, the VLR/CDA system might operate in a similar fashion; however, since the repertoire of AAD genes in this group of animals remains uncharacterized, their potential roles in the assembly of VLRA/C are unknown.…”
Section: The Origins Of the Rag Recombinase And Split Antigen Receptomentioning
confidence: 99%
“…Recently, following improvements in the methodology to rear in vitro -fertilized lampreys in the laboratory, in combination with highly efficient CRISPR/Cas9-mediated gene disruption, we have been able to directly examine a potential role of CDA2 in the VLRB assembly process in L. planeri [ 20 •• ]. We generated a large series of CDA2 -deficient L. planeri CRISPR/Cas9-induced mutants (crispants), exhibiting bi-allelic deleterious mutations of the CDA2 gene.…”
Section: Function Of the Cda2 Genementioning
confidence: 99%
See 3 more Smart Citations